The secret language of business : how to read anyone in 3 seconds or less - Hogan, Kevin (Hoboken, N.J. : J. Wiley, 2008)
A guide to reading body language and nonverbal communication for businesspeople. It brings the secrets of body language and nonverbal communication to the realm of business. It reveals the basics of body language and the power it has to influence attitudes, actions, and outcomes.
THE SECRET LANGUAGE OF BUSINESS; Contents; Acknowledgments; Introduction; About the Author; Chapter 1: The Secret Language of Business; Chapter 2: The Power of the Secret Language of Business; Chapter 3: Elements of Body Language; Chapter 4: Context and Environment; Chapter 5: Proxemics: The Secret Language of Business ... Up Close; Chapter 6: What Does Your Body Language Say about You?; Chapter 7: Personal Interactions; Chapter 8: The Secret Language of Inf luence in Business; Chapter 9: Secret Language of the Sexes; Chapter 10: Back Home with the Kids.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Body language; Nonverbal communication in the workplace; Kinesics; Langage du corps; Communication non verbale en milieu de travail; LANGUAGE ARTS & DISCIPLINES -- Communication Studies; Body language; Nonverbal communication in the workplace; dissertations; Academic theses; Academic theses; 2